2019
DOI: 10.1111/jnc.14680
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid levels of synaptic and neuronal integrity correlate with gray matter volume and amyloid load in the precuneus of cognitively intact older adults

Abstract: The main pathophysiological alterations of Alzheimer's disease (AD) include loss of neuronal and synaptic integrity, amyloidogenic processing, and neuroinflammation. Similar alterations can, however, also be observed in cognitively intact older subjects and may prelude the clinical manifestation of AD. The objectives of this prospective cross‐sectional study in a cohort of 38 cognitively intact older adults were twofold: (i) to investigate the latent relationship among cerebrospinal fluid (CSF) biomarkers refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
(178 reference statements)
0
7
0
Order By: Relevance
“…A cluster of CSF biomarkers, namely Tau, neurogranin, SNAP25 in this study, and also alpha‐synuclein, Visinin‐like protein‐1 (VILIP‐1), GAP43 and Beta‐secretase 1 (BACE‐1) levels are increased in MCI and AD and correlate highly with one another [6,9,36,37]. Even in cognitively normal individuals, these markers clustered with structural brain measures (MRI) in a factor analysis [38]. The strong correlation between CSF markers of cytosolic (Tau), presynaptic (SNAP25) and dendritic (neurogranin) proteins suggests that they may represent a coordinated aspect of neurodegeneration.…”
Section: Discussionmentioning
confidence: 86%
“…A cluster of CSF biomarkers, namely Tau, neurogranin, SNAP25 in this study, and also alpha‐synuclein, Visinin‐like protein‐1 (VILIP‐1), GAP43 and Beta‐secretase 1 (BACE‐1) levels are increased in MCI and AD and correlate highly with one another [6,9,36,37]. Even in cognitively normal individuals, these markers clustered with structural brain measures (MRI) in a factor analysis [38]. The strong correlation between CSF markers of cytosolic (Tau), presynaptic (SNAP25) and dendritic (neurogranin) proteins suggests that they may represent a coordinated aspect of neurodegeneration.…”
Section: Discussionmentioning
confidence: 86%
“…A recent study investigated a broad set of candidate biomarkers tracking distinct pathophysiological processes in patients with AD and reported a positive cross-sectional correlation between BACE1 CSF concentrations and NGR [20]. Interestingly, another group reported that the CSF NGR/BACE1 ratio, along with core AD biomarkers, displays good accuracy to distinguish between depression with cognitive impairment and AD dementia [29].…”
Section: Csf Bace1 and Synaptic Biomarkersmentioning
confidence: 99%
“…Studies investigating CSF BACE1 biomarkers and indicators of brain accumulation of Aβ, including CSF 42-amino acid forms of amyloid-β protein (Aβ42) and Aβ positron emission tomography (Aβ-AΒ-PET), do not show consistent results, as some studies did not find any significant association [ 10 , 14 , 16 , 17 ], while other studies showed significant correlations [ 18 20 ].…”
Section: Bace1 Biomarkers In the Cerebrospinal Fluid (Csf)mentioning
confidence: 99%
See 2 more Smart Citations